Paroikos como metáfora sobre a provisoriedade da vida - Färber, Sonia Sirtoli (2011)
This work is a result of an exegetical and bibliographical research, made in the biblical area, which investigates the term paroikoj as a metaphor about the temporality of life. Paroikoj (paroikos) is a Greek word that corresponds to the term rG (gēr), in Hebrew. The application of the term has a broad and variable spectrum, but the most important, and that is present in most of the concepts, is the one which refers to pilgrim, migrant and foreigner. In the first part, from the analysis of Greek and Hebrew texts, It is made a survey on the subject to whom the term is assigned to, their living conditions and social status. It was found that the migratory waves are an important phenomena in the history of Israel, and in the lives of biblical peoples who fought for space and land, and that being a resident foreigner used to limit the rights of individuals, placing them at an inferiority condition. In the Sociology of early Christianity, the frailty of the everyday realities and social exclusion, experienced by the Christians, gave them the title of paroikos. The self-consciousness of the Christians to be citizens of heaven led to the eschatological expectation of a heavenly city and strengthened the identity of paroikos. The variants and the evolution of the term in the Old Testament, in the New Testament and in the extra-biblical literature are highlighted. The concept of paroikoj is analyzed in its symbolic allocation and it is researched the occurrences of where it receives the eschatological connotation of temporality of life and expectation of immortality. The second part analyzes the notion of temporality of life in the stages of human development, from birth to death, through the losses and changes throughout life. The human being lives in a frailty state, and migrates from one condition to another, by a continuous exodus, each new phase meaning the death of the old one. With this postulate we present the several symbolic deaths that happen in the life of the same person and the points of contact with the concept of paroikos, meaning the one who is in transit. To conclude we present the rites of passage as important mechanisms for the elaboration of the symbolic mourning from the roaming conditions that mark human life.